Blau syndrome: Lessons learned in a tertiary care centre at Chandigarh, North India - Kumrah, Rajni; Pilania, Rakesh Kumar; Menia, Nitin Kumar; Rawat, Amit; Sharma, Jyoti; Gupta, Anju; Vignesh, Pandiarajan; Jindal, Ankur Kumar; Rikhi, Rashmi; Agarwal, Aniruddha; Gupta, Vishali; Singh, Surjit; et al. (Frontiers in Immunology, 2022)
Objectives Blau syndrome (BS) is a rare autoinflammatory disease characterized by arthritis, dermatitis, and granulomatous uveitis in early childhood. The study presents the clinical experience of patients with BS at a tertiary care centre in Chandigarh, North India. Methods Analysis of the clinical profile of patients of BS with NOD2 gene mutations under follow-up was carried out. Results Diagnosis of BS was genetically confirmed in 11 patients (10 children and one adult; six male and five female patients) from 10 families. The median age of onset of symptoms was 12 months (range, 4 months–4 years), while the age at diagnosis ranged from 2.3 to 26 years. The classic triad of arthritis, dermatitis, and uveitis was present in 6/11 (54.5%) patients. The frequency of arthritis, dermatitis, and uveitis was 100%, 81.8%, and 72.7%, respectively. The median age at diagnosis of ocular symptoms was 4 years (range, 2–26 years). Family history was noted in six families. Renal involvement was observed in two children. All patients in our cohort had the R334W variant in NOD2 gene. An asymptomatic carrier sibling with R334W mutation was identified in one family. Methotrexate was used as a first-line agent in all children. Adalimumab, which was commenced in five patients with uveitis, resulted in significant improvement in four patients. The total follow-up duration of the present cohort is 1,063.8 patient-months. Conclusions The possibility of BS should always be considered in patients with arthritis and early ocular involvement. Uveitis is often progressive and refractory to currently available therapies. Systemic involvement appears to remain a significant cause of morbidity and mortality.